Revisiting the diagnosis and treatment of Para Kala-azar Dermal Leishmaniasis in the endemic foci of Bangladesh. - Shomik Maruf; Soumik Kha Sagar; Md Masud Ur Rashid; Proggananda Nath; Md Sahidul Islam; Prakash Ghosh; Md Utba Rashid; Dinesh Mondal; Ahmed Abd El Wahed; Ariful Basher (PLoS ONE, 2023)
Para Kala-azar Dermal Leishmaniasis (Para-KDL) manifests the concomitant presence of Post Kala-azar Dermal Leishmaniasis and Visceral Leishmaniasis and works as a reservoir of infection. The study discusses the cases and their management and aims to address the gaps within existing methods of diagnosis and treatment. This retrospective cross-sectional study discusses 16 Para-KDL cases with one-year follow-up data, treated between 2012-2021 at the Surya Kanta Kala-azar Research Center, Bangladesh. We collected data from hospital records and used STATA 16 to analyze and see the frequency distribution and variable means. We found five patients without any history of kala-azar infection. All the patients were treated with 20 mg/kg Liposomal Amphotericin B in 4 divided doses except one with a history of AmBisome hypersensitivity. One year after treatment, all patients were free from skin lesions, with no hepatosplenomegaly, and observed significant improvement in BMI and hemoglobin levels. The Para-KDL patients are challenging to diagnose, and the relapse and treatment failure leishmania patients might have belonged to this rare group, contributing to their poor prognosis. Therefore, developing an appropriate diagnostic workflow and a new drug regimen is essential to sustain the success of our elimination efforts.